PREVALENCE OF GENERALIZED LIGAMENT LAXITY IN ADULT INDIAN POPULATION: A CROSS-SECTIONAL STUDY AND REVIEW OF LITERATURE - GOGIA, TUSHAR; DASGUPTA, TIRTHANKAR; RAJAN, ARAVIND; KHAN, IRFAN; KAJAL, PAWAN KUMAR; MISHRA, AJIT KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Generalized ligament laxity (GLL) is defined as increased range of motion across multiple joints in an individual. Its prevalence has been reported to be between 5% and 15%. Although there has been implication of increased prevalence in Indian population, there are relatively few studies related to the prevalence of GLL in adult Indian population. There is also a dearth of literature on, which specialty outpatient department (OPD), these patients commonly present to, with their complaints. The objective of this study was to assess the prevalence of GLL in adult Indian population. Methods: 5400 patients were selected from various OPDs of a tertiary care hospital after informed consent. After stratification for age and sex, Beighton’s score assessment was done. Results: Using the Beighton’s score of four or more, to assess the prevalence of generalized ligament laxity, a total of 735 (13.61%) participants had GLL in the entire study population of 5400. Significantly higher number of patients were found to have GLL from the sample recruited from orthopedic OPD (p=0.013) as compared to other OPDs. The highest Beighton’s score was 8/9, recorded in a 29-year female in the orthopedic OPD. It was observed that in all OPDs, the mean Beighton’s scores were higher in female than in male participants in each subgroup; also, there was a decline in mean scores with increase in age in all OPDs which can be inferred as a decrease in GLL with age. Conclusion: This study is the largest Indian study to investigate the prevalence of GLL in the adult population in India. The study found that there was a significant prevalence of GLL in the adult population especially in females compared to males in all ages, though prevalence of GLL reduced with age. This study has implications of prevention of injuries in people with GLL. Although orthopedic surgeons generally primarily manage the people with GLL, they do not have a high index of suspicion toward the same. Identifying these individuals and making a diagnosis regarding the same is problematic but doing so will help these individuals live a pain-free life.